COMMUNICATIVE APPROACH IN TEACHING FOREIGN LANGUAGES TO PRIMARY SCHOOL STUDENTS - Khosiyat Jurayevna Khakimova (Bright Mind Publishing, 2025)
This article analyzes the role, significance, and effective application of the communicative approach in teaching foreign languages, especially English, to primary school students. The communicative approach focuses on teaching a foreign language through natural communication processes, fostering students' speech activity and developing their social communication skills. The article presents lesson formats, methods, types of speech activities, and pedagogical tools based on the communicative approach.
Keywords: Primary education, foreign language, communicative approach, speech activity, communication, interactive teaching, CLT, ESL.